Comparative Analysis of Percutaneous Nephrostomy and Double J Stenting in Upper Urinary Tract Obstruction with Acute Kidney Injury: A Tertiary Hospital Based Prospective Study - Manzoor Ahmad; Vivek Pachauri; Saif Quaiser; Wasif Md Ali; Imad Ali; Adnan Habib (National Board of Examinations Journal of Medical Sciences)
Background: Upper urinary tract obstruction is a serious condition that can lead to significant renal impairment if not managed promptly. Emergency urinary diversion is crucial for alleviating obstruction and preserving renal function. This study investigates various emergency urinary diversion techniques, compares their outcomes, and evaluates factors influencing recovery. Methods: We conducted a prospective study involving 106 patients diagnosed with obstructive uropathy at Jawaharlal Nehru Medical College, Aligarh Muslim University. Patients were classified into upper urinary tract obstruction and lower urinary tract obstruction. 70 patients of the upper urinary tract obstruction cases were further managed by either percutaneous nephrostomy (PCN) or double-J (DJ) ureteral stenting diversion procedures. 68 out of 70 upper urinary tract obstruction underwent either of the two procedures. Clinical, demographic, and laboratory parameters were analysed in such patients, and their outcomes were assessed at one and three months. Results: The study included 68 out of 106 patients with a mean age of 48 years. Most patients presented with acute kidney injury (AKI) and had symptoms of loin pain and haematuria. Both PCN and DJ stenting were equally effective in managing upper tract obstruction, with no significant differences in improvement of the laboratory parameters (e.g. Hemoglobin, Serum Creatinine, estimated Glomerular Filtration Rate, Blood Urea Nitrogen) between the two techniques at one and three months. Associated factor like age was associated with unfavourable outcomes. Conclusion: Emergency urinary diversion via PCN or DJ stenting effectively manages upper urinary tract obstruction, with comparable outcomes. Early intervention and management of underlying conditions are critical for optimal renal recovery and prevent irreversible kidney damage.